Allogeneic hematopoietic cell transplantation improves outcome of adults with t(6;9) acute myeloid leukemia - results from an international collaborative study - Kayser, Sabine; Krämer, Alwin; Ho, Anthony Dick; Müller-Tidow, Carsten; Schlenk, Richard Friedrich (Haematologica, 2020)
Acute myeloid leukemia with t(6;9)(p22;q34) is a distinct entity accounting for 1-2% of acute myeloid leukemia cases. A substantial proportion of these patients have a concomitant FLT3-ITD. While outcomes are dismal with intensive chemotherapy, limited evidence suggests allogeneic hematopoietic cell transplantation may improve survival if applied early during first complete remission. We report on a cohort of 178 patients with t(6;9)(p22;q34) within an international, multicenter collaboration. Median age was 46 (range: 16-76) years, acute myeloid leukemia was de novo in 88%, FLT3-ITD was present in 62%, and additional cytogenetic abnormalities in 21%. Complete remission was achieved in 81% (n=144), including 14 patients who received high-dose cytarabine after initial induction failure. With a median follow-up of 5.43 years, estimated overall survival at 5 years was 38% (95%-CI, 31-47%). Allogeneic hematopoietic cell transplantation was performed in 117 (66%) patients, including 89 in first complete remission. Allogeneic hematopoietic cell transplantation in first complete remission was associated with higher 5-year relapse-free and overall survival as compared to consolidation chemotherapy (45% [95%-CI, 35-59%] and 53% [95%-CI, 42-66%], vs. 7% [95%-CI, 3-19%] and 23% [95%-CI, 13-38%]. For patients undergoing allogeneic hematopoietic cell transplantation, overall survival rates at 5 years did not differ whether performed in first (53% [95%-CI, 42-66%]), or second complete remission (58% [95%-CI, 31-100%]; n=10) or with active disease/relapse (54% [95%-CI, 34-84%]; n=18) (P=0.67). Neither FLT3-ITD nor additional chromosomal abnormalities impacted survival. In conclusion, outcomes of t(6;9)(p22;q34) acute myeloid leukemias are poor with chemotherapy, and can be substantially improved with allogeneic hematopoietic cell transplantation.
Pre-published: April 19, 2019
Gesehen am 27.01.2020